FACTORS INFLUENCING TOURISTS’ PERCEPTIONS AT MILKINDO AGROTOURISM, KEPANJEN, MALANG REGENCY - Hadi, Kemal Akshaliano; Siti Azizah (PT. Jurnal Center Indonesia Publisher, 2025)
Milkindo Agrotourism, located in Malang Regency, was an educational tourism destination that combined modern livestock and agricultural activities. This study examined the influence of attraction, accessibility, amenity, and ancillary factors on visitor perceptions. Data were collected in February 2025 through questionnaires distributed to 100 visitors. The research instruments were tested for validity and reliability, and classical assumption tests were performed to ensure the appropriateness of multiple linear regression analysis. The results revealed that visitors rated the clarity of registration information and memorable experiences the highest. Regression analysis showed that attraction significantly negatively affected visitor perception, while accessibility, amenity, and ancillary factors had significant positive effects. This indicated that enhancing accessibility, amenity, and ancillary improved visitor satisfaction, whereas increasing attraction elements unexpectedly lowered visitor perception. In conclusion, effective management of attraction, accessibility, amenity, and ancillary was essential to foster positive visitor perceptions and enhance the competitiveness of Milkindo Agrotourism as a leading educational tourism destination. The study recommended continuous innovation and improvement to support sustainable development in education-based agrotourism.